NILAI-NILAI KESETARAAN GENDER DAN ETIKA DALAM NOVEL WAJAH SEBUAH VAGINA - Arju - Susanto (Populis : Jurnal Sosial dan Humaniora, 2017)
Unlike women emancipation in advanced nations in North America and Western Europe, the movement of Raden Ajeng Kartini’s movement in Indonesia has successfully enriched the tradisional culture with the Western spirit of modernity. The paper is an account of the novel Wajah Sebuah Vagina  (2004) by Naning Prawoto. The themes of the novel are ethics and gender equality. Using qualitative method along with the psychology of art-work, the study finds that fifty percents of 38 scenes deal with ethics and another fifty percents with gender. Secondly the study finds that the novel has successfully portrait typical women with ambition and forgetting social norms and values of the society that lead her to her failure; the implied message is the need to adopt modernism and at the same retain the “modernity” within her own culture.Keywords : Ethics,  gender equality, modernism, novel